Les Difficultes Inherentes A La Mobilisation Des Connaissances Mathematiques Dans La Physique, Cas De La Mecanique Au College - Raouf, Khadija; Belazzaar, Imad; Radi, Morad; Moussetad, Mohamed; Talbi, Mohammed (European Scientific Journal, ESJ, 2016)
This study focuses on the difficulties of pupils in final year of college cycle (14-17 years) to mobilize mathematical knowledge in mechanical modeling activities. The objective is to try to understand the dynamics of the transfer of mathematical knowledge in modeling the concept of "speed" and the notion of "force." To do this, we developed two individual written questionnaires to a sample of pupils. One focuses on mathematics and the other mechanics. To better interpret some results, we held individual interviews with a sample of pupils. Analysis and interpretation of the results of the questionnaires and interviews show that the mathematical knowledge mobilization difficulties are due in the first hand to the non mastery of this knowledge in mathematic courses and the second hand to the fact that pupils aren’t conscious of the linkages which exist between mathematic and physic. The students having answered correctly seem adopting memorization strategies than cognitive strategies conducive to the transfer.